Soil Organisms Activities in Red Onion Cultivation with Application of Plant Extract Suspension and Compost - Icha Deska Rani; Dermiyati Dermiyati; Radix Suharjo; Ainin Niswati; Darwin Hasibaran Pangaribuan (UNIVERSITY OF LAMPUNG, 2022)
Agro-industrial waste such as banana weevil, pineapple rhizome, and empty fruit bunches of oil palm has not been utilized properly, even though the waste can be processed into liquid organic fertilizer after extracting the beneficial microorganisms contained in it. This research aimed to observe and study soil organisms’ activity after applying plant extract suspensions and compost types. The research was conducted at the Integrated Field Laboratory and Soil Science Laboratory, Faculty of Agriculture, University of Lampung. The treatments were designed in a 3 × 3 factorial design in a Randomized Block Design with three replications. The first factor was the plant suspension extracts derived from banana weevil, pineapple rhizome, and oil palm empty fruit bunches, while the second factor was the compost in the form of solid compost and liquid compost. The results showed the activity of soil organisms in the form of respiration, soil microbial carbon biomass, soil microbial population, and mesofauna population, which was applied to a suspension of plant extracts from pineapple rhizome, given the highest yield. Furthermore, the bacterial phosphate dissolution index and the diversity of soil mesofauna applied to liquid compost were higher than those of solid compost or without compost. There was no interaction between the application of plant extract suspension and the compost types on the soil organism’s activity.